2015
DOI: 10.5194/acp-15-1161-2015
|View full text |Cite
|
Sign up to set email alerts
|

Use of a global model to understand speciated atmospheric mercury observations at five high-elevation sites

Abstract: Abstract. Atmospheric mercury (Hg) measurements using the Tekran® analytical system from five high-elevation sites (1400–3200 m elevation), one in Asia and four in the western US, were compiled over multiple seasons and years, and these data were compared with the GEOS-Chem global model. Mercury data consisted of gaseous elemental Hg (GEM) and "reactive Hg" (RM), which is a combination of the gaseous oxidized (GOM) and particulate bound (< 2.5 μm) (PBM) fractions as measured by the Tekran® system. We used a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 59 publications
7
81
0
Order By: Relevance
“…The observed TM profiles are often similar to GEM profiles. Inside the PBL, oxidized mercury (OM) (here, OM is defined as the sum of all oxidized forms of mercury including model species GOM, PBM, and any mercury in the aqueous phase) concentrations are very low and mostly between 20 and 100 pg m −3 in Europe and North America, even in source regions with high anthropogenic emissions (e.g., coal-fired power plants) (Xu et al, 2016;2013;Gay et al, 2013;Tørseth et al, 2012;Prestbo and Gay, 2009;Weiss-Penzias et al, 2015). In China, PBM concentrations up to 1000 pg m 3 and GOM concentrations up to 100 pg m 3 have been observed, but no aircraft observations in the PBL and the LFT are available for this region : (Fu et al, 2015Sprovieri et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed TM profiles are often similar to GEM profiles. Inside the PBL, oxidized mercury (OM) (here, OM is defined as the sum of all oxidized forms of mercury including model species GOM, PBM, and any mercury in the aqueous phase) concentrations are very low and mostly between 20 and 100 pg m −3 in Europe and North America, even in source regions with high anthropogenic emissions (e.g., coal-fired power plants) (Xu et al, 2016;2013;Gay et al, 2013;Tørseth et al, 2012;Prestbo and Gay, 2009;Weiss-Penzias et al, 2015). In China, PBM concentrations up to 1000 pg m 3 and GOM concentrations up to 100 pg m 3 have been observed, but no aircraft observations in the PBL and the LFT are available for this region : (Fu et al, 2015Sprovieri et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For atmosphere-terrestrial exchange, GEOS-Chem treats the evasion and dry deposition of GEM separately . Dry deposition is parameterized with a resistance-inseries scheme (Wesely, 1989). In addition, an effective GOM uptake by sea salt aerosol is also included over the ocean .…”
Section: Geos-chemmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the theoretical doubts of significance of GEM oxidation under atmospheric conditions by O 3 and OH radical, atomic Br is of great relevance to the atmospheric oxidation of GEM is certain (Hynes et al, 2009;Subir et al, 2011Subir et al, , 2012Weiss-Penzias et al, 2015). In particular, for the HgBr * intermediate, Dibble et al (2012) have shown the potential importance of reactions with NO 2 , HOO, ClO and BrO.…”
Section: Mercury Oxidationmentioning
confidence: 99%
“…Observations in mountain areas can provide insight into: a) long-range transport of air pollutants; b) impact of acid rain on alpine forests and their response to pollution; c) fog scavenging and aerosol removal from direct cloud impact with terrain slopes; d) role of orographic convection and its effects on precipitation; e) heterogeneous ice nucleation of various aerosol types (Wrzesinsky and Klemm, 2000;Avila and Rodà, 2002;Igawa et al, 2002;Thalmann et al, 2002;Baumgardner et al, 2003;Burkard et al, 2003;Bayraktar and Turalioglu, 2005;Kim et al, 2006;Fischer et al, 2007;Budhavant et al, 2009;Calvo et al, 2012;Pawar et al, 2012;Hallar et al, 2013;Li et al, 2014;Conen et al, 2015;Weiss-Penzias et al, 2015;Sarkar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%